Basal cell skin cancer with sebaceous glands nevus: clinical presentation and differential diagnostics - Y. V. Karacheva; T. N. Guzey; T. A. Yakovleva; A. N. Smykova; Y. U. Vinnik (Vestnik Dermatologii i Venerologii, 2017)
The description of two clinical cases of basal cell skin cancer, which developed against the background of a nevus of sebaceous glands.The article reflects the clinical features and criteria for the differential diagnosis of pigmented form of basal cell skin cancer.